iGREEN-RISK MANAGEMENT: INTEGRATED RISK MANAGEMENT MODEL FOR SUSTAINABLE GREEN TOURISM AT SUKOMAKMUR AGROTOURISM MAGELANG - Idah Kusuma Dewi; Dyan Triana Putra; Athalya Davina Ramadhani Purwanto; Ryan Fadhila Firdaus; Nina Mistriani (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to develop an integrated risk management model called iGreen-Risk Management to support sustainable green tourism at Sukomakmur Agrotourism in Magelang, Indonesia. Using a Participatory Action Research approach, the research involves key stakeholders through focus group discussions, interviews, field observations, and document analysis over one year. The model is designed to identify, analyze, evaluate, and mitigate environmental, social, and economic risks in green tourism development. The expected outcome is a practical framework that helps agrotourism operators manage risks while promoting environmental conservation, community well-being, and long-term economic sustainability. The study’s novelty lies in creating the first integrated risk management framework specifically tailored for green tourism within an agrotourism context, combining participatory methods with comprehensive risk management principles not yet explored in sustainable tourism research.